Pedagogical Competence of Pre-Service Teachers in Implementing PJBL (Project Based Learning) - Natalia Anggrarini (Wiralodra English Journal, 2018)
This study described and explained the pedagogical competence of Pre service English teachers in Indonesia in implementing Project Based Learning in teaching writing narrative text during apprenticeship program. It described the implementation of Project Based Learning (PJBL) done by pre-service teachers. The steps in project based learning were getting the idea, design the project, tune the project, do the project and exhibit the project. This study used qualitative approach by describing the implementation of the PJBL. The subjects were four teacher candidates of VI semester English Department in Wiralodra University. The findings showed that the concept of PJBL not completely actualized in the classroom. This condition lead to problematic situation for the pre-service teachers. Comprehensive understanding should be taken by pre-service teacher in implementing PJBL in teaching writing narrative text. It is needed to achieve the target of English learning. Thus a deeper understanding of PJBL is needed not only the technical implementation but also cognitive implementation.